Serum iron levels in correlation with serum lead, and serum calcium levels in diabetic patients - Wasan Abdulkareem Abbas (College of Pharmacy / Mustansiriyah University, 2012)
Recent medical researches suggest that there may be a link between iron levels and diabetes . The objective of this study is to measure serum iron levels in diabetic patients and compared with healthy controls .The study also include the measurement of both serum calcium ,and serum lead levels in diabetic patients and the correlation between these two elements and the disease ,and the correlation between these elements and iron level in diabetic patients. This study included 30 patients had diabetes were submitted to the out patients clinic of Baghdad Teaching Hospital. Those patients were varying in their ages (30-70 years) and duration of disease (1-22 years) compared with 20 apparently healthy controls (non diabetic), with the same range of age. Calcium, lead, and iron estimation were done by atomic absorption method. In this study there is no significant changes were found in both serum lead levels of the patients compared with the controls and serum iron levels of the patients compared with the controls , While there is a significant changes in serum calcium levels of the patients compared with the controls p ˂ 0.0001. Also there is inverse correlation between serum calcium and serum iron (r=-0.398) , a weak inverse correlation between serum lead and serum iron (r=-0.069),and a direct weak correlation between serum calcium and serum lead(r=0.027) were found in the patients. The role of iron in diabetes development still unclear, and the patients should carefully use iron supplements particularly patients with long duration of the disease.